2020
DOI: 10.1111/jpc.15090
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary approach to paediatric aerodigestive disorders: A single‐centre longitudinal observational study

Abstract: Aim: Aerodigestive clinics (ADCs) are multidisciplinary programmes for the care of children with complex congenital or acquired conditions affecting breathing, swallowing and growth. Our objective was to describe the demographic, clinical, etiological and investigational profile of children attending the inaugural ADC at a tertiary paediatric centre in Queensland. Methods: Children referred to the ADC at Queensland Children's Hospital from August 2018 to December 2019 were included. Data on clinical, growth an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 20 publications
0
7
1
Order By: Relevance
“…We did not find a significant relationship for aspiration in the present cohort, but it is possible that this is related to our older pediatric population, where swallowing dysfunction associated with developmental immaturity may have been outgrown 35 . Other groups have reported increased incidence of bronchiectasis in aerodigestive center populations and therefore the underlying conditions commonly seen in this population might put these patients at increased risk 12 …”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…We did not find a significant relationship for aspiration in the present cohort, but it is possible that this is related to our older pediatric population, where swallowing dysfunction associated with developmental immaturity may have been outgrown 35 . Other groups have reported increased incidence of bronchiectasis in aerodigestive center populations and therefore the underlying conditions commonly seen in this population might put these patients at increased risk 12 …”
Section: Discussioncontrasting
confidence: 59%
“…With the growth of multidisciplinary aerodigestive centers, many patients with persistent pulmonary symptoms undergo triple airway endoscopy as an initial part of their workup before consideration of chest CT 49 . This approach commonly includes flexible bronchoscopy with bronchoalveolar lavage and the results are typically interpreted in the multidisciplinary aerodigestive context 8,12–14 . Prior studies have shown an association between bronchiectasis and BAL neutrophil count and the results our ROC analysis are similar 24,50,51 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have adopted a multidisciplinary model of care including pulmonology, gastroenterology, surgery, speech therapy, physiotherapy, respiratory scientists, and clinical nurse practitioners. 42 As with any diagnostic procedure, the sensitivity will be dependent on the skill of the proceduralist. We acknowledge that the positive TEF identification rate may be more dependent on the expertise and procedural dexterity of the bronchoscopist compared with the radiologic techniques.…”
Section: Discussionmentioning
confidence: 99%